HUBUNGAN INDEKS MASA TUBUH DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI PUSKESMAS SEI LANGKAI KOTA BATAM TAHUN 2021 - Aprilya Roza Werdani; Desy Desy; Dino Himawan; Evelina Siregar (Lembaga Pengembangan Kinerja Dosen, 2022)
Hypertension is an increase in high blood pressure where systolic < 140 mmHg and diastolic < 90 mmHg. In Indonesia, hypertension ranks first, amounting to 63.5% (Rikesdas, 2018). Factors that can cause high blood pressure are being overweight followed by a lack of exercise, and consuming foods that are fatty and high in salt. This study aims to determine the relationship between body mass index and the incidence of hypertension in the elderly at the Sei Langkai Health Center, Batam city in 2021. The design of this study used an analytical observational research design with a cross sectional. Respondents in this study 64 respondents. The sampling technique used is purposive sampling. The results of the chi-square test showed p value = 0.000 (<0.05) so that Ho was rejected, this indicates a relationship between body mass index and the incidence of hypertension in the elderly at the Sei Langkai Public Health Center Batam city in 2021. The conclusion of this study is the elderly who have weight overweight is at risk for hypertension. It is recommended to health care workers to be able to provide health education about the importance of maintaining an ideal weight for the elderly.